Optimising central bank behaviour in a stochastic environment with uncertain credibility : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Economics at Massey University - Croke, Hilary (Massey University, 1998)
Central bank credibility is defined for the purposes of this thesis as the belief held by agents that the central bank will not renege on its commitment to the specified monetary policy objective. Agents' perceptions on both the integrity and ability of the central bank to achieve and maintain price stability affect the determination of actual inflation via expected inflation. In the past, theoretical models have attempted to capture credibility effects through the application of game theory to assimilate the strategic interaction that occurs between the central bank, the government and agents. For the most part, these models are simple in structure and combined with the limitations commonly attributed to game theory have been heavily criticised. The results derived from empirical analyses of credibility have also been subject to debate due to the directly unobservable nature of credibility. In the past, such analyses have used a variety of measures to proxy credibility effects. While it is generally accepted that expected inflation would perhaps be the most accurate indicator, expectations are equally as subjective as credibility. The results presented in this thesis are derived from simulations of the Reserve Bank's macroeconomic model used for forecasting and policy analysis (FPS). Given that the central bank faces uncertainty regarding its true level of credibility, it is necessary for policymakers to assume the level of credibility when formulating monetary policy. Depending on the specific disturbance that hits the economy, the combined effect of the bank's assumed and actual level of credibility can ultimately determine the success of the implemented policy. The main motivation of this thesis is to determine the extent to which the central bank benefits when it is aware of the fact it truly has credibility or whether the optimal policy response should always be based on the premise of no credibility. In order to provide a more realistic analysis, stochastic simulations of FPS are used. In this case, the central bank observes a combination of five impulses simultaneously hit the economy in the current period and taking into account the effects of the impulses from previous periods, formulates monetary policy depending on its assumed level of credibility. Despite the added dimension of uncertainty the central bank faces surrounding the occurrence of future shocks, the results indicate that the increase in output loss normally associated with a harsh policy response is minimal. By assuming a lack of credibility and thereby adopting a prudent approach to monetary policy, inflation variability is substantially reduced without any significant increase in output variability.
Keywords: Econometric models; Monetary policy; Inflation (Finance); Banks and banking, Central; New Zealand; Econometric models